Demand Projections for the Fund's Concessional Resources. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Projections of demand for concessional loans under the Poverty Reduction and Growth Trust (PRGT) are subject to a high degree of uncertainty. The Fund's financial support to low-income countries (LICs) is both cyclical and lumpy. Moreover, there are important structural changes underway that are likely to affect the frequency, nature, and size of Fund concessional lending. As a result, simple extrapolations from historical lending volumes are misleading. This paper reviews factors underlying historical lending trends and develops a methodology that can narrow down the range of possible longer-term demand scenarios.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Demand; Financial Support; Fund; Lending; PP; Congo, Democratic Republic of the